(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This study explores the Stop Bullying theatre initiative, implemented as part of a summer camp program designed to promote literacy and social cohesion through participatory drama. Grounded in a Design-Based Research framework, the project engaged 13 children (aged 8–12) in reading, rehearsing, and staging Claudia Kumpfe’s play Alone! School as a Crime Scene!, which addresses bullying and peer dynamics between childrenin schools. A variety of methods were employed, including pre- and post-intervention surveys on bullying and social cohesion, daily field diaries from theatre coaches, and qualitative feedback from children and parents. The results demonstrate statistically significant improvements in the participants’ sense of equality, comfort, and group belonging, supported by qualitative accounts of empathy, cooperation, and new friendships. Coaches’ observations indicated increased fluency, motivation, and expressive oral reading. The findings highlight theatre pedagogy’s potential to foster inclusion, solidarity, and democratic participation while also offering low-threshold entry points for literacy engagement. This study underscores the value of integrating socially relevant themes into participatory arts projects to cultivate both cognitive and socio-emotional development in inclusive educational settings.